Desafios e perspectivas para a consolidação do PROEJA como política pública: uma análise do PROEJA no Instituto Federal de São Paulo - Castro, Ana Laura da Silva (Universidade Federal de São Carlos, 2026)
This dissertation analyzes the challenges and prospects for consolidating the National Program for the Integration of Professional Education with Basic Education in the Youth and Adult Education Modality (PROEJA) as a public policy, based on its implementation at the Federal Institute of Education, Science and Technology of São Paulo (IFSP). The study is grounded in the understanding that, although PROEJA was conceived as a policy oriented toward the integration of basic education and vocational education, comprehensive human development, and the guarantee of the right to education for young and adult workers, its implementation within educational institutions is shaped by structural, political, and pedagogical contradictions. The research adopts a predominantly qualitative approach, grounded in Historical-Dialectical Materialism and informed by a historical-critical perspective on education, combining quantitative data on the number of places offered, enrollment rates, and dropout rates with documentary analysis of legislation, institutional documents, and data from the Plataforma Nilo Peçanha (PNP). Semi-structured interviews were also conducted with individuals involved in the management and implementation of PROEJA at IFSP and were analyzed using Content Analysis, based on the methodological contributions of Bardin and Silva and Fossá. The findings indicate that the difficulties involved in consolidating PROEJA at IFSP do not constitute an isolated phenomenon. Rather, they reflect the structural weakening of the policy itself, shaped by its decree-based nature, the discontinuity of government priorities, and the insufficiency of stable funding mechanisms. In the context analyzed, PROEJA tends to occupy a peripheral position, characterized by weaknesses in its institutionalization process and by a significant dependence on the commitment of teachers and administrators directly involved in its implementation. The data reveal low occupancy rates of the places offered and high dropout rates, associated both with the students' concrete living and working conditions and with limitations in the implementation of the policy. The analyses further indicate that student retention is affected by factors such as long working hours, family responsibilities, and the rigidity of institutional regulations. At the same time, the interviews show that strategies such as active outreach, articulation with other networks, curriculum flexibilization, modular course organization, and socio-pedagogical support can contribute to expanding access, retention, and students' chances of academic success. It is concluded that the consolidation of PROEJA as a public policy depends on strengthening its institutionalization, ensuring adequate funding, and developing coordinated strategies capable of making access, retention, and the effective realization of integrated education viable as a right of the working class.
Challenges and Prospects for the Consolidation of PROEJA as a Public Policy: An Analysis of PROEJA at the Federal Institute of São Paulo
Keywords: Educação de Jovens e Adultos; PROEJA; IFSP; Educação Profissional e Tecnológica; Políticas Públicas; CIENCIAS HUMANAS::EDUCACAO; 4. Educação de Qualidade; 10. Redução das Desigualdades